Effective stabilization of CLA by microencapsulation in pea protein. (1st February 2015) - Costa, A.M.M.; Nunes, J.C.; Lima, B.N.B; Pedrosa, C.; Calado, V.; Torres, A.G.; Pierucci, A.P.T.R.
Highlights: Pea protein is a biocompatible, sustainable and natural wall material. Pea protein concentrate particles showed better physical–chemical characteristics. Maltodextrin addition in the wall system improved microparticles functionalities. Maltodextrin addition in the wall system did not improve CLA oxidation stability. The microencapsulation process stabilized CLA stored during 2 months. Abstract: CLA was microencapsulated by spray drying in ten varied wall systems (WS) consisting of pea protein isolate or pea protein concentrate (PPC) alone at varied core:WS ratios (1:2; 1:3 and 1:4), or blended with maltodextrin (M) and carboxymethylcellulose at a pea protein:carbohydrate ratio of 3:1. The physical–chemical properties of the CLA microparticles were characterised by core retention, microencapsulation efficiency (ME), particle size and moisture. CLA:M:PPC (1:1:3) showed the most promising results, thus we evaluated the effect of M addition in the WS on other physical–chemical characteristics and oxidative stability (CLA isomer profile, quantification of CLA and volatile compounds by SPME coupled with CG-MS) during two months of storage at room temperature, CLA:PPC (1:4) was selected for comparisons. CLA:M:PPC (1:1:3) microparticles demonstrated better morphology, solubility, dispersibility and higher glass-transition temperature values. M addition did not influence the oxidative stability of CLA, however its presence improved physical–chemical characteristics necessary for food applications.